Swedish Pupils’ Perspectives on Emergency Remote Teaching during COVID-19 - A Qualitative Study - Ringer, Noam; Kreitz-Sandberg, Susanne (International journal of educational research open, 2022)
Due to the COVID-19 pandemic, schools in many countries were forced to stop face-to-face teaching and switch to emergency remote teaching (ERT). The aim of this study, based on semi-structured interviews with upper secondary-school pupils in Stockholm, was to explore how Swedish pupils perceive their ERT and to understand their preconditions for learning. We found variations among pupils with regard to how they perceived their new morning routine, the increased flexibility in structuring their day, the flexibility to choose their workplace at home, and the decreased control by their teachers. While some perceived the increased flexibility as challenging, others appraised it as a possibility to be more independent. With regard to their classmates, all participants perceived difficulties learning from each other in ERT. Identified difficulties involved comparing one's performance to that of classmates, having deep discussions, encouraging each other, and organizing themselves in a group. The results are discussed in relation to previous studies, and are interpreted through the lenses of the Designs for Learning Theory.